Electrochemical Determination of the Superoxide Anion Radical Using a Gold Nanoparticle Poly(3, 4-Ethylenedioxythiophene) Ferrocyanide Multiwalled Carbon Nanotube Glassy Carbon Electrode. (3rd July 2018) - Wu, Cong; Cui, Min; Chen, Xiangmin; Zhai, Miao; Ren, Jujie; Yu, Congcong; Yu, Xudong; Ji, Xueping
ABSTRACT: A superoxide anion radical ( O 2 ⋅ − ) electrochemical sensor based on a gold nanoparticle/[Fe(CN)6 ] 4– anionic doped poly(3, 4-ethylenedioxythiophene)/multiwalled carbon nanotube composite modified glassy carbon electrode was fabricated. The sensor was characterized by scanning electron microscopy, cyclic voltammetry (CV), and electrochemical impedance spectroscopy. It showed remarkable performance toward the electrocatalytic reduction of O 2 ⋅ − . The amperometric response was linear with the O 2 ⋅ − concentration from 4.3 to 179.4 µM with a correlation coefficient of 0.995. The prepared electrochemical sensor achieved a sensitivity of 1450 µA mM −1 cm −2 and a limit of detection of 1.5 µM at a signal-to-noise ratio of three. Excellent selectivity, reproducibility and stability were observed because of the positive synergistic effect of gold nanoparticles, poly(3, 4-ethylenedioxythiophene)–[Fe(CN)6 ] 4− and multiwalled carbon nanotubes.